Critical Analysis of the article: "Dogs as Role Models" by Richard Curwin (2013)
The article “Dogs as Role Models: A lesson in classroom management” written by Richard Curwin on august, 17th 2012, is a research where the author exposes an experience that he had many years ago with his dog and how he could associate this event with the classroom management and the behavior of his students.